Un reino de ceniza al alcance del viento: José Ángel Valente y la división del canto (1961-1982) (TEST Ticontre. Theory Text Translation, 2020)
A look at the vast corpus of critical studies dedicated to the poetry of José Ángel Valente reveals that certain assumptions made by critics have led to certain books receiving extensive attention while others have largely been overlooked or underappreciated. A key example of this sort of overlooked work is a pair of hybrid texts made up of selections of poems previously published in books alongside groups of newly published poems. Neither exclusively anthologies nor new collections, books like Sobre el lugar del canto and Estancias offered Valente an opportunity to pause and take stock of his work while also charting new aesthetic paths. These books allow readers to ask important questions regarding the ways in which poems are packaged and framed and how this impacts the way we engage with them as critics and readers.